Islamisasi Ilmu Pengetahuan Dalam Perspektif Filsafat Pendidikan Islam - Muhammad Syaifullah; Azimah Az-zahra; Husna Ibrahim; Rinanti Ito Pohan (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
Islamization is to make or bring something into Islam and make it Islam Beginning and several decades. Syed M. Naquib al Attas developed that idea into the "Islamisan" project which he introduced at the First World Conference on Islamic Education in Mecca in 1977. The goal and Islamization of science itself is to protect Muslims from knowledge that has been tainted and misleading, causing confusion, and there are 12 systematic steps to apply science to the implementation of science on education in Islam namely on the institutional aspect that is the institutional aspect of mu and the intention is the unification of the two educational systems, and on the aspect of kumkum namely studying kunkulam is not left to just one team, but requires ahh ahh in their field , this discussion must start from the beginning of Islamization, on the aspect of educators, namely in terms of educators being placed at the appropriate level, meaning that competent and professional they are valued as they should be. The method used in writing this journal is using the Yakm library research method by weaving various sources. references to get the right data in explaining the topic of discussion.